2021
DOI: 10.1002/jor.25140
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between tibial articular cartilage, in vivo external joint moments and static alignment in end‐stage knee osteoarthritis: A micro‐CT study

Abstract: Biomechanical factors (e.g., joint loading) have a significant role in the progression of osteoarthritis (OA). However, some relationships between in vivo joint loading indices and tibial cartilage thickness are conflicting. This study investigated relationships between pre‐operative in vivo external knee joint moments, joint alignment and regional tibial cartilage thickness using micro‐CT in subjects with end‐stage knee OA. Tibial plateaus from 25 patients that underwent knee replacement for OA were micro‐CT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
(147 reference statements)
0
1
0
Order By: Relevance
“…Therefore, it is important to determine the effect of knee alignment on cartilage wear at each anatomic location. With that in mind, Rapagna et al [9] used CT scans to evaluate the effect of overall alignment on anteromedial, posteromedial, anterolateral, and posterolateral cartilage wear and reported that varus alignment was associated with anteromedial wear of the tibia. However, to the best of my knowledge, no study has evaluated the anatomy of the femur and tibia in more detail, including intercondylar lesions.…”
mentioning
confidence: 99%
“…Therefore, it is important to determine the effect of knee alignment on cartilage wear at each anatomic location. With that in mind, Rapagna et al [9] used CT scans to evaluate the effect of overall alignment on anteromedial, posteromedial, anterolateral, and posterolateral cartilage wear and reported that varus alignment was associated with anteromedial wear of the tibia. However, to the best of my knowledge, no study has evaluated the anatomy of the femur and tibia in more detail, including intercondylar lesions.…”
mentioning
confidence: 99%